Unified European higher medical degrees. Issue 822 (April 1994) - Breimer, L. H.; Mikhailidis, D. P.
Abstract : Unequal access to higher medical degrees, which are important for career advancement, is a problem that is likely to plague UK medicine as integration within Europe proceeds. This paper analyses the characteristics of M.D.s at the Royal Free Hospital School of Medicine and proposes a solution of creating a common European doctorate.